MAKNA SIMBOL UPACARA PERNIKAHAN ADAT SUKU LEMBAK DAN RELEVANSINYA DENGAN NILAI-NILAI KEISLAMAN (STUDI TRADISI DI DESA KEMBANG SERI KECAMATAN TALANG EMPAT KABUPATEN BENGKULU TENGAH) - Ahmad Fikram Ahmad (Sekolah Pasca Sarjana IAIN Bengkulu, 2017)
The results of the study explained, Firstceremonial procession namely: consensus night, the ceremony, the bride besanding, bridal becampur, menyalang, and keduri disband the committee. Both forms of symbolsKetan fry, Lenguai,4-5 rice dishes, all existing side dishes, umbrellas, fans, Sarafal Anam, seven bars cigarette, cigarette case (where cigarettes), limes letter (lemon), flowers, water, a small basin, saffron rice portion,Chicken.Third In the implementation wedding ceremony tribal Lembak raised many Islamic values which contain values of divinity, the value of deliberation, the value of mutual help and the value of moral education in life married to each other along together, love one another and help each other to live a married life.